The quality of maternity care services as experienced by women in the Netherlands - Wiegers Therese A (BMC, 2009)
Abstract Background Maternity care is all care in relation to pregnancy, childbirth and the postpartum period. In the Netherlands maternity care is provided by midwives and general practitioners (GPs) in primary care and midwives and gynecologists in secondary care. To be able to interpret women's experience with the quality of maternity care, it is necessary to take into account their 'care path', that is: their route through the care system. In the Netherlands a new tool is being developed to evaluate the quality of care from the perspective of clients. The tool is called: 'Consumer Quality Index' or CQI and is, within a standardized and systematic framework, tailored to specific health care issues. Within the framework of developing a CQI Maternity Care, data were gathered about the care women in the Netherlands received during pregnancy, childbirth, and the postpartum period. In this paper the quality of maternity care in the Netherlands is presented, as experienced by women at different stages of their care path. Methods A sample of 1,248 pregnant clients of four insurance companies, with their due date in early April 2007, received a postal survey in the third trimester of pregnancy (response 793). Responders to the first questionnaire received a second questionnaire twelve weeks later, on average four weeks after delivery (response 632). Based on care provider and place of birth the 'care path' of the women is described. With factor analysis and reliability analysis five composite measures indicating the quality of treatment by the care provider at different stages of the care path have been constructed. Overall ratings relate to eight different aspects of care, varying from antenatal care by a midwife or GP to care related to neonatal screening. Results 41.5 percent of respondents remained in primary care throughout pregnancy, labor, birth and the postpartum period, receiving care from a midwife or general practitioner, 31.3% of respondents gave birth at home. The majority of women (58.5%) experienced referral from one care provider to another, i.e. from primary to secondary care or reverse, at least once. All but two percent of women had one or more ultrasound scans during pregnancy. The composite measures for the quality of treatment in different settings and by different care providers showed that women, regardless of parity, were very positive about the quality of the maternity care they received. Quality-of-treatment scores were high: on average 3.75 on a scale ranging from 1 to 4. Overall ratings on a 0 - 10 scale for quality of care during the antenatal period and during labor, birth and the postpartum period were high as well, on average 8.36. Conclusion The care path of women in maternity care was seldom straight forward. The majority of pregnant women switched from primary to secondary care and back at least once, during pregnancy or during labor and birth or both. The results of the quality measures indicate that the quality of care as experienced by women is high throughout the care system. But with regard to the care during labor and birth the quality of care scores are higher when women know their care provider, when they give birth at home, when they give birth in primary care and when they are assisted by their own midwife.